2022
DOI: 10.1017/hpl.2022.9
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-compact post-compressor on-shot wavefront measurement for beam correction at PHELIX

Abstract: In order to reach the highest intensities, modern laser systems use adaptive optics to control their beam quality. Ideally, the focal spot is optimized after the compression stage of the system in order to avoid spatio-temporal couplings. This also requires a wavefront sensor after the compressor, which should be able to measure the wavefront on-shot. At PHELIX, we have developed an ultra-compact post-compressor beam diagnostic due to strict space constraints, measuring the wavefront over the full aperture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This figure is based on the original version by J. B. Ohland [20] and its modification by M. Malki [21] . approx.…”
Section: Phelix -Current Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…This figure is based on the original version by J. B. Ohland [20] and its modification by M. Malki [21] . approx.…”
Section: Phelix -Current Statusmentioning
confidence: 99%
“…Typically, the first 30 DM modes are used during correction. The loop is closed by a SHS in a beam diagnostic that uses the equivalent-target-plane concept [40] . In a proof-ofconcept study, the capability of on-shot measurement was demonstrated and an improvement of the focused intensity on target by a factor of 3 to 5 was shown, also taking care of aberrations introduced during the daily operation by incomplete thermal relaxation of the MA of PHELIX between shots.…”
Section: Wavefront Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…( 1), which corresponds to the convergence condition. Once the image distribution is obtained, the test object can be directly obtained from the conjugation relationship between the object and image space [34][35][36][37] .…”
Section: Array Focusing and Phase-shift Imagingmentioning
confidence: 99%